Voting on the Budget Deficit: Comment - Peletier, Ben D; Dur, Robert A. J; Swank, Otto H (American Economic Review, 1999)
In this comment, it is argued that a balanced-budget rule may cause underinvestment. As a consequence, such a rule is not ex ante efficient: in order to achieve the ex ante optimal outcome, it would be necessary to add an extra rule for the level of public investment. Unfortunately, however, such an investment rule is likely to be very difficult to implement in practice. When there are no rules to prevent underinvestment, it is no longer clear whether a balanced-budget rule is beneficial or not. In some cases, the cost of low levels of investment outweigh the benefits of a balanced budget.